High degree of supervision improves adherence to inhaled corticosteroids in children with asthma - Geun Mi Park; Hye Won Han; Hee Se Kim; Jae Youn Kim; Eun Lee; Hyun-Ju Cho; Song-I Yang; Young-Ho Jung; Soo-Jong Hong; Hyung Young Kim; Ju-Hee Seo; Jinho Yu (Korean Pediatric Society, 2015)
PurposeAdherence to treatment with inhaled corticosteroids (ICS) is a critical determinant of asthma control. The objective of this study was to assess factors that determine adherence to ICS therapy in children with asthma.MethodsFifty-eight children with asthma, aged 5 to 16 years, used ICS with or without a spacer for 3 months. Adherence rates as measured from questionnaires and canisters, asthma symptom scores, and inhalation technique scores were assessed every 30 days. The degree of supervision by caregivers was assessed at day 30.ResultsAdherence rates measured using canisters were lower at day 60 than at day 30 (P=0.044) and did not change thereafter (74.4%±17.4% at day 30, 66.5%±18.4% at day 60, and 67.4%±22.2% at day 90). Adherence rates at days 60 and 90 and during the total study period were significantly different when measured by using questionnaires versus canisters (P<0.001, P=0.022, and P=0.001, respectively). In the comparison of adherence rates repeatedly measured at days 30, 60, and 90 and adherence rates during the total study period among the 3 groups, adherence rates in the high-degree supervision group were significantly higher than those in the low-degree supervision group (82.0±16.0 vs. 66.1±14.5, 75.4±14.4 vs. 56.2±18.4, 75.0±18.3 vs. 55.0±19.7 [P=0.027]; 77.9±12.2 vs. 59.1±11.4 [P=0.021]) after adjustment for sex and age.ConclusionThe level of caregiver supervision is an important factor affecting adherence to ICS therapy in children with asthma. Therefore, a high degree of supervision may be required to increase adherence to ICS therapy in children with asthma.